A method to analyze soccer offensive sequences - Ziskind, F.; Marche, A.; Misuta, M.; Barros, R.; Cunha, S. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
There is a range of possibilities to analyze the soccer game in relation to physical-technical-tactical aspects. The importance of going toward the goal rapidly since the recovery of possession was defended by Grehaigne et al (1996). The main technique to analyze soccer attack speed in literature was presented by Yue et al (2008). The aim of this study was to propose a method to analyze offensive sequences in soccer based on goal progression velocity (GPV) and goal progression indicator (GPI).